Research on task offloading and resource allocation in edge computing network of RIS assisted UAV based on Lyapunov - KUANG Zhufang; GUO Yujing; DENG Xiaoheng (Tongxin xuebao)
To address the problem that unmanned aerial vehicle (UAV) face complex time-varying fading channels, which could affect wireless transmission, a joint optimization problem of UAV's trajectory, reconfigurable intelligent surface (RIS) phase shift, offloading slot allocation, CPU frequency allocation, and user equipment transmission power was constructed. In order to solve the constructed problem, the stability constraints of UE and UAV task queues were transformed, and the multi-timeslot stochastic optimization problem was transformed into a deterministic optimization problem for each time slot. A JORL optimization method based on Lyapunov optimization and block coordinate descent (BCD) method was proposed. Firstly, the phase shift of RIS was solved based on the triangle inequality and the closure expression was obtained. Then the technology of transforming the non-convex into the convex problem was used to solve the offloading slot allocation, CPU frequency allocation and user equipment transmission power. Finally, the trajectory of UAV was solved based on successive convex approximation (SCA) method. Simulation results show that JORL has better performance in ensuring queue stability and reducing energy consumption.